A Dual Threshold Based Opportunistic Spectrum Access Policy with Non-Ideal Spectrum Sensing - Xiaodong Peng; Limin Xiao; Xiaofeng Zhong; Shidong Zhou (Dianxin kexue)
To effectively improve the throughput performance of secondary user in cognitive networks, a dual threshold based opportunistic spectrum access policy was proposed, which could be implemented under the condition that secondary user had non-ideal spectrum sensing capability. The proposed policy can take both channel quality information of secondary user and the inaccurate channel occupation information into account, to make secondary user access the channel in sensed idle and busy states with different channel quality thresholds. Based on this, the throughput performance of secondary user can be improved significantly by utilizing the transmission opportunities with good channel quality. With this policy, an optimization problem maximizing the effective throughput of secondary user with interference constraint for protecting primary user was formulated, and the optimal channel quality thresholds were derived under non-ideal spectrum sensing. Simulation results demonstrate the effective throughput performance of secondary user with non-ideal spectrum sensing capability can be improved significantly by implementing the proposed dual threshold based opportunistic spectrum access policy.